PENERAPAN AROMATERAPI LAVENDER PADA LANSIA HIPERTENSI DENGAN GANGGUAN POLA TIDUR - yusniar; Maria Saragi; Laydi Herdinda Sinabutar; Josephany Amaria Hutagalung (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Hypertension is defined as a systolic blood pressure (SBP)more than 140 mmHg or a diastolic blood pressure (DBP)more than 90 mmHg. Hypertensive patients often complain of difficulty sleeping and heart palpitations, leading to body aches, headaches, fatigue, and disturbed daily activities in the morning. This is caused by an increase in cortisol hormone, which destabilizes blood pressure, potentially leading to complications and impairing the patient's quality of life. A non-pharmacological approach to reduce sleep pattern disturbances due to hypertension is the use of lavender aromatherapy. This study aims to determine whether lavender aromatherapy is effective in reducing sleep pattern disturbances experienced by hypertensive patients experienced. Case Study Methods: This was a qualitative descriptive study using a case study approach with two female participants over 55 years old who experienced hypertension with sleep pattern disturbances. The research was conducted in Sipan Village, Sarudik Sub-district, Central Tapanuli Regency, in 2025. Data collection involved PSQI observation, interviews, physical examinations, and documentation review. Results: A decrease in sleep pattern disturbances was observed after 7 days of therapy for both patient one and patient two. Patient one's score decreased from 15 to 2, and patient two's score decreased from 15 (poor sleep quality) to 2, indicating good sleep quality for both participants. Conclusion and Recommendation: The effectiveness of lavender aromatherapy in reducing sleep pattern disturbances in hypertensive patients has been proven. It is expected that this therapy continues to be used for its effectiveness in addressing sleep complaints.